Editorial: Sustainable Fashion in India: An Overview - Vincent Jaiwant, Sunanda (Ushus Journal of Business Management, 2022)
Lately, a greater number of industries are moving towards sustainability, sustainable products and process. Sustainable fashion is a term that is quite a in vogue lately. Study reveals that the fashion industry is the second largest industry polluting the environment. It is now driving several eco-conscious brands and individuals to opt-out of fast fashion and adopt more planet-friendly strategies. Sustainable fashion is catching up like fire in India. Sustainable, eco-conscious brands from across the country are organizing online as well as offline sales of their goods. India has witnessed many homegrown fashion and accessory brands that are moving towards sustainable clothing and fashion. The fashion industry has joined the bandwagon in the last few years to remain in the good books of their customers and to resonate with the sustainability revolution.